Prevalence of celiac disease in latin america: a systematic review and meta-regression. - Rafael Parra-Medina; Nicolás Molano-Gonzalez; Adriana Rojas-Villarraga; Nancy Agmon-Levin; Maria-Teresa Arango; Yehuda Shoenfeld; Juan-Manuel Anaya (PLoS ONE)
Background Celiac disease (CD) is an immune-mediated enteropathy triggered by the ingestion of gluten in susceptible individuals, and its prevalence varies depending on the studied population. Given that information on CD in Latin America is scarce, we aimed to investigate the prevalence of CD in this region of the world through a systematic review and meta-analysis. Methods and findings This was a two-phase study. First, a cross-sectional analysis from 981 individuals of the Colombian population was made. Second, a systematic review and meta-regression analysis were performed following the Preferred Reporting Items for Systematic Meta- Analyses (PRISMA) guidelines. Our results disclosed a lack of celiac autoimmunity in the studied Colombian population (i.e., anti-tissue transglutaminase (tTG) and IgA anti-endomysium (EMA)). In the systematic review, 72 studies were considered. The estimated prevalence of CD in Latin Americans ranged between 0.46% and 0.64%. The prevalence of CD in first-degree relatives of CD probands was 5.5%. The coexistence of CD and type 1 diabetes mellitus varied from 4.6% to 8.7%, depending on the diagnosis methods (i.e., autoantibodies and/or biopsies). Conclusions Although CD seems to be a rare condition in Colombians; the general prevalence of the disease in Latin Americans seemingly corresponds to a similar scenario observed in Europeans.